The Emotional Divergent–Convergent Thinking Program (EDICOP): Design, Implementation, and Results - Goretti Soroa; Aitor Aritzeta; Alexander Muela; Nekane Balluerka; Arantxa Gorostiaga; Jone Aliri (European Journal of Investigation in Health, Psychology and Education, 2020)
In a social environment that requires young people to adapt to increasingly demanding situations, emotional education and creativity training may be key for both personal development and academic performance. Given that there are currently no known interventions that develop emotional and creative skills simultaneously in a youth population, the main objective of this study was to design, implement, and evaluate the Emotional Divergent–Convergent Thinking Program (EDICOP). The study design was quasi-experimental with a non-equivalent control group and pretest–posttest measures. The participants included 196 students between 16 and 24 years of age belonging to two centers of higher education. Our results showed that the EDICOP contributed to the improvement of the participants’ divergent-proactive style, positive affectivity, emotional predisposition, and attention, as well as to their preference for cognition. Overall, the EDICOP is, therefore, both relevant and useful, and further research on the mood–creativity link is merited to generate new contexts in higher education for the promotion of both the emotional and creativity dispositions and self-awareness, by combining three basic psychological processes (emotion, cognition, and motivation).